2004
DOI: 10.1021/jp049662r
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Methanol on Pt Nanoparticles Dispersed on RuO2

Abstract: Pt-modified RuO2 was prepared by a sol−gel procedure on titanium substrates in the form of thin films of ∼2-μm thickness. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analyses showed that these films actually consist of Pt nanoparticles dispersed in RuO2 and that neither metallic Ru nor Pt−Ru alloy are present on the surface. Electrodes with different Pt:Ru nominal compositions were prepared and their electrocatalytic activity for the oxidation of methanol was investigated by potential sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 45 publications
6
68
0
Order By: Relevance
“…The ligand effect assumes that the energy level of the metal catalyst is modified so that the binding strength with the metal and adsorbed CO is weakened, resulting in a reduction in overpotential for CO oxidation. The possibility that some nanostructured ruthenium oxides (expressed as RuO x H y or RuO 2 •xH 2 O in the literature) may act as co-catalysts has attracted interest and debate [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Several studies have suggested that the binary PtRu alloy structure is not a prerequisite for obtaining the highest activity, and partially oxidized ruthenium species (RuO x ) that are present in the PtRu/C catalysts may contribute to the anodic activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand effect assumes that the energy level of the metal catalyst is modified so that the binding strength with the metal and adsorbed CO is weakened, resulting in a reduction in overpotential for CO oxidation. The possibility that some nanostructured ruthenium oxides (expressed as RuO x H y or RuO 2 •xH 2 O in the literature) may act as co-catalysts has attracted interest and debate [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Several studies have suggested that the binary PtRu alloy structure is not a prerequisite for obtaining the highest activity, and partially oxidized ruthenium species (RuO x ) that are present in the PtRu/C catalysts may contribute to the anodic activity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the binary PtRu alloy structure is not a prerequisite for obtaining the highest activity, and partially oxidized ruthenium species (RuO x ) that are present in the PtRu/C catalysts may contribute to the anodic activity [4][5][6]. Enhancement in methanol oxidation activity has been reported for Pt-RuO 2 composite catalysts although the activity of such material is in general lower than that of PtRu alloy [7][8][9][10][11][12][13][14]. On the contrary, other studies have reported that ruthenium oxide is inactive for CO oxidation [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Even in the case of Pt-Ru bimetallic alloys, currently considered the best materials for the oxidation of methanol, it has been recently suggested that bulk quantities of electron-proton conducting RuOxHy would produce a significantly better electrocatalytic activity [42,43]. Moreover, results obtained recently in our laboratory show that, in fact, Pt nanoparticles dispersed in a RuO 2 matrix exhibit a quite significant electrocatalytic activity for methanol oxidation [44].…”
Section: Electrocatalytic Propertiesmentioning
confidence: 81%
“…Takai et al have briefly reported on the synthesis of mesoporous Ru black with surface area of 62 m 2 g -1 via lyotropic crystal templating as the end member of the Pt-Ru alloy [23]. In addition to metallic Ru, high surface area ruthenium oxide is also an important material for various applications, including electrocatalysts for chlorine evolution [24], electrochemical capacitor electrodes [25][26][27][28][29], as well as fuel cell electrocatalysts [30][31][32][33][34][35][36][37][38][39]. The small particle size (1-2 nm) and the existence of appreciable pores are important requirements for the high capacitance [40][41][42].…”
Section: Introductionmentioning
confidence: 99%